Terminal chromosome 4q deletion syndrome in an infant with hearing impairment and moderate syndromic features: review of literature - Vona, Barbara (BioMed Central, 2014)
BACKGROUND: Terminal deletions of chromosome 4q are associated with a broad spectrum of phenotypes including cardiac, craniofacial, digital, and cognitive impairment. The rarity of this syndrome renders genotype-phenotype correlation difficult, which is further complicated by the widely different phenotypes observed in patients sharing similar deletion intervals. CASE PRESENTATION: Herein, we describe a boy with congenital hearing impairment and a variety of moderate syndromic features that prompted SNP array analysis disclosing a heterozygous 6.9 Mb deletion in the 4q35.1q35.2 region, which emerged de novo in the maternal germ line. CONCLUSION: In addition to the index patient, we review 35 cases from the literature and DECIPHER database to attempt genotype-phenotype correlations for a syndrome with great phenotypic variability. We delineate intervals with recurrent phenotypic overlap, particularly for cleft palate, congenital heart defect, intellectual disability, and autism spectrum disorder. Broad phenotypic presentation of the terminal 4q deletion syndrome is consistent with incomplete penetrance of the individual symptoms.